Teknik Bilimler Meslek Yüksekokulu Öğrencilerinin Temel Matematik Başarılarının Değerlendirilmesi. - CİVCİK, Levent; KISA, Mustafa; LORASOKKAY, M. Ali (Selcuk University Social Sciences Institute / Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2017)
Students attending Vocational Schools of Higher Education are given courses suing two methods, namely theoretical and practical. Basic Mathematics is one of the highly important courses that fall within the group of theoretical courses. Importance of mathematics cannot be denied given that Vocational Schools of Higher Education were established to meet the need for qualified intermediate staff members. This study aimed to investigate students' views concerning mathematics course and factors affecting success in this course. Assessments were made, especially taking into account the achievements of students who were admitted through examination and those who were admitted through open admission. In this study, evaluations were made on the basis of various questions asked of students attending Selcuk University Vocational School of Technical Sciences (VSTS) Department of Computer Programming. As a result of this study, students' points of views concerning mathematics and their assessments in this regard were revealed. In the process of data collection, a questionnaire which was prepared in an effort to determine students' views regarding the mathematics course and statistical data obtained from the Office of Students Affairs were made use of. Likert Scale assessment range was used in the evaluation of the data to arrive at conclusions.